Pelatihan Membuat Boneka Jari Bagi Ibu-Ibu POMG TKIT Irsyadul Ibad Pandeglang - Veny Agustina Prianggita; Nenden Suciyati Sartika (Jurnal Pengabdian Pada Masyarakat, 2018)
TRAINING ON MAKING FINGER PUPPETS FOR MOTHERS OF POMG TKIT IRSYADUL IBAD PANDEGLANG. In general women have a role and greater influence compared to men in educating her children at home. So, it is very important when mothers get more knowledge and skills to improve the quality. Community programs that researchers have done is create a training “Finger Puppet making skills” to the Moms POMG TKIT Irsyadul ‘Ibad. Methods undertaken by using a Participatory training method. In participatory training used the so-called cycle of learning from experience (experimental learning cycle). Results and discussion will be illustrated through images cycle of learning from experience. Finger puppet making skills training proved necessary because it can serve as a medium for storytelling to the child’s mother.